An unusual detection of tert‐butyl‐4‐anilinopiperidine‐1‐carboxylate in seizures of falsified 'Xanax' tablets and in items in a suspected heroin seizure submitted by Irish law enforcement. Issue 9 (15th July 2020) - May, Colette; Downey, Carol; Power, John D.; Kavanagh, Pierce V.
Abstract: The identification of tert ‐butyl‐4‐anilinopiperidine‐1‐carboxylate (4‐anilinopiperdine‐ t ‐BOC or 4‐AP‐ t ‐BOC) in many seized falsified 'Xanax' tablets has been reported after being encountered in forensic casework in late 2019 and early 2020 in Ireland. This substance was also detected in a pink powder submitted for analysis in March 2020. The pink powder was part of a larger seizure comprising brown powders which contained morphine or diamorphine (heroin) or a type of counterfeit heroin or heroin adulterant (known as 'bash'). Novel benzodiazepines and other substances are being detected as ingredients in falsified benzodiazepine tablets more frequently on the illicit market. The detection of 4‐AP‐ t ‐BOC in benzodiazepine tablets is noteworthy and 4‐AP‐ t ‐BOC is added to the list of adulterants found in benzodiazepine tablets emerging in Europe. The presence of 4‐AP‐ t ‐BOC in both falsified 'Xanax' and powdered seizures is unusual, and analytical data are presented to assist with the identification of this compound in suspected illicit substances. The presence of 4‐AP‐ t ‐BOC in the tablets was confirmed using gas chromatography–mass spectrometry and liquid chromatography–mass spectrometry analyses, and spectral fragmentation pathways were suggested. To the authors' best knowledge, information about the biological activity of 4‐AP‐ t ‐BOC is not available. The removal of the t‐ BOC protecting group yields 4‐anilinopiperidine which has been reported to be involved in the synthesis of fentanyl. Abstract : 4‐Anilinopiperidine‐ t ‐BOC was detected in falsified 'Xanax' tablets and powder seized by Irish law enforcement in 2019/2020. This compound could potentially be utilized in the illicit production of fentanyl. Analytical data are presented to assist in the identification of this compound in illicit substances.